2000
DOI: 10.1051/lait:2000135
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of whey drainage kinetics during soft cheese manufacture in relation with the physicochemical and technological factors, pH at renneting, casein concentration and ionic strength of milk

Abstract: -The kinetics of whey drainage of Camembert soft cheese was studied using an instrumented drainage device to record the pH and the weight of the whey with a variation coefficient amounting to 1.8% during the first 100 min and 0.34% at the end of drainage. Drainage data were fit with a two step equation to obtain a descriptive model of the drainage kinetics. The effect of the pH at renneting, the casein concentration and the ionic strength on the drainage kinetics was investigated with a 2 level experimental de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
(46 reference statements)
4
15
0
Order By: Relevance
“…In the third phase, between the 6th and the 23rd hour, only 4% of the total were collected. These changes are well known and confirm previous works [4,11]. Depending on the experiment, a final quantity ranging between 36 kg and 37.4 kg of serum was collected, with an average of 36.8 ± 1.9 kg.…”
Section: Typical Evolution and Repeatabilitysupporting
confidence: 88%
See 1 more Smart Citation
“…In the third phase, between the 6th and the 23rd hour, only 4% of the total were collected. These changes are well known and confirm previous works [4,11]. Depending on the experiment, a final quantity ranging between 36 kg and 37.4 kg of serum was collected, with an average of 36.8 ± 1.9 kg.…”
Section: Typical Evolution and Repeatabilitysupporting
confidence: 88%
“…Kaytanli et al [6] showed the effects of milk pH, temperature, and calcium and rennet concentrations on the kinetics of draining. Recently, Daviau et al [4] studied and modelled the effects of milk pH, casein concentration and ionic strength of milks on the kinetics of soft cheese drainage.…”
Section: Introductionmentioning
confidence: 99%
“…(42) A classical example of syneresis is the production of cheese. (57)(58)(59)(60) Syneresis also takes place during the coagulation of blood and in many other important biological processes. Syneresis can be induced by increasing the concentration of the polymer, and begins after this concentration passes a certain critical value.…”
Section: Deposition Of Silicamentioning
confidence: 99%
“…Control of whey expelled during cheese-making, including the control of syneresis from the curd grains when they are in the cheese vat, is a crucial step in cheese processing as the moisture content of the curd at the drainage step influences the quality of the cheese (Daviau et al, 2000). The extent of syneresis depends on many factors like milk composition, calcium equilibria, casein concentration, pH, temperature, gel firmness at cutting time and size of the curd grains (Grundelius, Lodaite, Östergren, Paulsson, & Dejmek, 2000;Patel, Lund, & Olson, 1972).…”
Section: Introductionmentioning
confidence: 99%